1961
DOI: 10.1002/cjce.5450390106
|View full text |Cite
|
Sign up to set email alerts
|

The horizontal pipeline flow of equal density oil‐water mixtures

Abstract: The horizontal flow of equal density oil‐water mixtures was investigated in a 1‐inch diameter laboratory pipeline. Oils of viscosities 6.29, 16.8 and 65.0 centipoise were used in the experiments. Flow patterns, holdup ratios and pressure gradients were investigated for a range of superficial oil velocity from 0.05 to 3.0 ft./sec. and a range of superficial water velocity from 0.1 to 3.5 ft./sec, with input oil‐water ratios ranging from 0.1 to 10.0. Similar series of flow patterns were observed for each oil and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
189
1
9

Year Published

1996
1996
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 288 publications
(212 citation statements)
references
References 5 publications
13
189
1
9
Order By: Relevance
“…In pressure-driven two-layer/core-annular flows, several authors have conducted linear stability analyses by considering the fluids to be immiscible 4,[6][7][8] and miscible. 3,[9][10][11][12] This problem was also studied by many researchers experimentally 13,14 and numerically. [15][16][17][18] In miscible core-annular flows, the thickness of the more viscous fluid layer left on the pipe walls and the speed of the propagating "finger" were experimentally investigated by many authors [19][20][21][22][23] and the axisymmetric and "corkscrew" patterns were found.…”
Section: Introductionmentioning
confidence: 95%
“…In pressure-driven two-layer/core-annular flows, several authors have conducted linear stability analyses by considering the fluids to be immiscible 4,[6][7][8] and miscible. 3,[9][10][11][12] This problem was also studied by many researchers experimentally 13,14 and numerically. [15][16][17][18] In miscible core-annular flows, the thickness of the more viscous fluid layer left on the pipe walls and the speed of the propagating "finger" were experimentally investigated by many authors [19][20][21][22][23] and the axisymmetric and "corkscrew" patterns were found.…”
Section: Introductionmentioning
confidence: 95%
“…In a somewhat different context, i.e. for liquid-liquid flow through a cylindrical tube, Hu and Joseph (1989) argue that the emulsification of water into oil, as observed experimentally by Charles et al (1961), is a direct consequence of shear mode instability.…”
Section: Shear Mode Instabiliomentioning
confidence: 99%
“…These have included linear stability analyses for horizontal [6,7,[17][18][19] and vertical pipes [5,20], accounting for viscosity and density contrasts, experiments [21,22] and numerical simulations in straight [9,10,23] and corruagated pipes [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%